Methods, Techniques and Tools to Support Software Project Management in High Maturity - Cerdeiral, Cristina Teles; Santos, Gleison (RelaTe-DIA, 2017)
High maturity in software development is associated to statistical control of critical subprocesses performance and the use of gained predictability to manage projects with better planning precision and monitoring control. Although maturity models such as CMMI mention some statistical and other quantitative approaches, methods and techniques that can support project management in high maturity, they do not provide details about them neither present their available types. Therefore, there is a lack of knowledge on how to support software process improvement initiatives to choose and use statistical and other quantitative approaches, methods and techniques on such context. The objective of this study is to identify different approaches, methods and techniques that can assist on managing projects in high maturity. By conducting a systematic literature mapping on major data sources, we identified 75 papers describing 101 contributions. We briefly describe identified approaches, methods and techniques grouped by similar types and provide some analysis regarding technological maturity stage and evaluation method, and supported development methods and characteristics and process/indicator area in which they were applied. We hope this information can fill some of the statistical and quantitative knowledge gap about the actual types of approaches, methods and techniques being proposed, evaluated, experimented and adopted by organizations to assist on quantitative project management in high maturity.